Effect of vendors' socio-demography and other factors on hygienic practices of street food shops. Issue 4 (4th July 2021) - Kundu, Satyajit; Banna, Md. Hasan Al; Sayeed, Abu; Akter, Sharmin; Aktar, Achia; Islam, Md Azharul; Proshad, Ram; Khan, Md Shafiqul Islam
ABSTRACT: Street food business provides low-cost ready-made meals and employments for the marginal people in developing countries. But the lack of good hygiene in the street food shops is a major concern for consumer. This research examined the effect of the socio-demography of vendors and other factors on hygienic practices in street food shops. This cross-sectional study was conducted among 137 street food vendors in the Barishal and Patuakhali cities of Bangladesh. A pre-structured questionnaire was used to collect information on sellers and shops. A logistic regression model was employed to check the effect of the factors on the hygiene practice score of respondents. Among the vendors, only 27.7% recruited an extra employee in their shops and 43.1% had a good score on the hygienic practices. Regression analysis showed that vendors who completed secondary education (AOR = 3.308; 95% CI: 1.560 to 7.015) and recruited extra employee (AOR = 3.381; 95% CI: 1.465 to 7.800) were more likely to have a higher score than the counterparts. The overall hygiene practices of the vendors were not satisfactory. The education of sellers and the employee's assistance will boost the hygienic standards of the street food shops.